1998
DOI: 10.1177/0145482x9809200703
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Social Networks and the Employment of Visually Impaired College Graduates

Abstract: This study examined the relationship between the employment status of visually impaired college graduates in Great Britain and their social networks, both formal and informal. The unemployed graduates had less extensive support networks to help them find jobs; used contacts in less directive ways; and socialized in more structured, group-centered ways than did the employed graduates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 7 publications
3
11
1
Order By: Relevance
“…One of the strongest individual predictors of the range of a social network was “employment.” Employed participants tended to have more extended social networks than those of unemployed participants. This finding is consistent with previous research that employment status appears to play a significant role, as employed individuals with visual impairments were found to have larger and more supportive networks than the unemployed individuals with visual impairments (Roy et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…One of the strongest individual predictors of the range of a social network was “employment.” Employed participants tended to have more extended social networks than those of unemployed participants. This finding is consistent with previous research that employment status appears to play a significant role, as employed individuals with visual impairments were found to have larger and more supportive networks than the unemployed individuals with visual impairments (Roy et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Employment status has also been found to be a significant factor in social support, as employed individuals with visual impairments appear to have more supportive networks than do unemployed individuals (Roy et al, 1998). In addition, a low level of independence in adults with visual impairment seems to lead to overprotective behaviors from network members as a form of negative social support (Cimarolli, 2006), whereas independence in mobility of adolescents with visual impairment influences the amount of social support (Kef et al, 2000).…”
Section: Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these studies included transition-age youth in addition to adults. Research conducted within the past 15 years has supported the importance of the following variables to employment: higher level of education, including having received an educational certificate or degree; work experience; good self-rated health; lower functional disability; and better social support, including wider supportive social networks and more helpful family support (Capella-McDonnall, 2005;Cimarolli & Wang, 2006;Kirchner, Schmeidler, & Todorov, 1999;Roy, Dimigen, & Taylor, 1998). Other research has supported the importance of social support and computer technology skills in helping persons with VI retain employment (Crudden, 2002).…”
mentioning
confidence: 99%
“…O'Neill et al [57] (1998) also reported that in their sample of individuals with traumatic brain injury, employment status was strongly re-lated to perceived quality of life and level of involvement in home and leisure activities. Roy, Dimigen and Taylor [58] studied the social networks and employment of visually-impaired college graduates and found that those who were employed had a larger social network, were more likely to spend time socially outside of home in bars, social clubs, or informally with friends, and did so more frequently than the unemployed.…”
Section: Employment and Psychosocial Adjustment To Disabilitymentioning
confidence: 99%